Material Test Comparison of Pure Aluminum (Al) and Pure Aluminum-Coated (Al) with Silver (Ag) Substrat Using Electroplating Method - Aming Sungkowo; Trikolas Trikolas; Rosyid Ridlo Al Hakim; Slamet Riyadi; Yanuar Zulardiansyah Arief; Ariep Jaenul (ARRUS Journal of Engineering and Technology, 2021)
Electroplating uses aluminum material, where it’s easy to obtain, lighter, and cheaper than other metals. The research goal was to determine the ability of the electric current to power aluminum (Al) coated with silver (Ag) by the electroplating method, to determine the effect of the magnitude of the electric current and the length of time the coating process took on the weight of Al coated with Ag and to determine the strength of the metal Al after tested using Brinnell test. The method used is to compare pure Al and pure Al coated with Ag by electroplating at different currents to determine the effect of the electroplating process. A Brinnell test was carried out to determine the hardness of the Al material after electroplating. The results are the amount of current that flows during the electroplating is directly proportional to the thickness of the electroplating layer attached to the Al surface. If the electroplating process uses a large current, the attached layer will look rough and not smooth, which also affects the material testing by using the Brinnell method. The Brinnell test proves that the hardness value of the Al material is directly proportional to the thickness of the layer.